MEDCO BIOETHANOL PLANT IN KOTABUMI LAMPUNG AND ITS PRODUCTION IMPACTS TO THE SURROUNDING PEOPLE - suharta, herliyani (Agency for the Assessment and Application of Technology)
Government of Indonesia (GOI) has stated its intention to support the development of alternative energy sources including biofuel. As the basis for such a development, GOI through Ministry of Energy and Mineral Resources (MEMR) has discussed it in many energy forums in order to shape a national blueprint for bioethanol and biodiesel. In 2004, total consumption of fossil fuel: gasoline, diesel, kerosene, pertamax and pertamax plus, were 60.06 million kilo Liters (kL), while total production from the existing refineries in Indonesia is only 44.9 million kL in 2005, leaving a deficit that should be imported. Responding this situation, Medco Energi is committed to invest and initiate its entry by developing Indonesia s first multi-feedstock bioethanol production plant that able to produce ethanol from cassava-derived starch and sugarcane molasses. Biogas produced by the waste treatment facility will be used to optimize the overall energy efficiency. By mid of 2007, it is planned to produce 180 kL industrial-grade ethanol daily and a fuel-grade ethanol will be produced as the market grow. The paper is also described the socio economics and macroeconomic impact of this activities that representing a case study in developing countries that giving subsidize for fossil fuel to their people.